Esensi Komunikasi ditinjau dari Perspektif Aksiologi : The Essence of Communication Reviewed from an Axiological Perspective - Fitra Khairinnahda; Afdhal Dzikri; Mahdum Adanan; Jimmi Copriady (Undiksha, 2026)
Communication science is a scientific discipline that studies the principles of information delivery and opinion formation in society. Philosophy plays a crucial role as a foundation for science and an integral part of life, including communication. Through an axiological framework, the philosophy of science examines communication from the perspective of ethical and aesthetic values, thus providing a foundation for determining the goals, methods, and impacts of communication. However, communication practices in society often do not optimally apply the axiological dimension. This study aims to analyze the essence of communication from an axiological perspective and to examine its implications within communication. The method used is a conceptual-philosophical study based on literature. The results of the study indicate that axiology plays a crucial role in communication, thus achieving good, effective communication and a harmonious society